Barbara Czarniawska : At home in translation - Corvellec, Hervé ; 0000-0001-7491-8816 (puntOorg, 2025)
Some get lost in translation; Barbara Czarniawska was at home in it. Early in my career, she helped me translate my vague sense that organizational performances were stories into the more precise concept of narratives which, allowed me to connect organizational studies with literary theory. Through her teaching, notably her course From Field to Desk, she guided PhD students in translating fieldwork into theoretical insights, balancing methodological rigor with openness. Drawing on Latour and Callon, Czarniawska framed translation as a process of adapting ideas across contexts, for example, shaping practices of urban management. Her work on overflow, a mistranslation of rugby’s cadrage-débordement, demonstrated how concepts can evolve productively even when repurposed. Her action net theory, a translation of Actor-Network Theory, redefined organizations as dynamic webs of interconnected actions. A polyglot, Czarniawska also translated scholarly and literary texts into Polish, merging academic rigor with personal passion. For her, translation was never merely literal; it was a creative act that makes it possible for ideas to travel, transform, and flourish across boundaries.
Keywords: Barbara Czarniawska